The acceptance of abstract algebra in the USSR, as viewed through periodic surveys of the progress of Soviet mathematical science - Hollings, C (Elsevier, 2015)
During the several decades of the USSR's existence, Soviet mathematicians produced, at intervals, a number of volumes of survey articles which provide us with a series of ‘snapshots’ of Soviet mathematics down the years. In this paper, I introduce these volumes as a resource for historians of Soviet mathematics, and consider the picture they paint of the development of abstract algebra in the USSR, paying particular attention to the aspects in which these surveys differ from later, retrospective accounts of Soviet algebra.